Total Body Photography and Sequential Digital Dermoscopy in Pregnant Women - Gabriela M. Martins-Costa (Mattioli1885, 2019)
Background: Melanocytic nevi can vary in size and number in pregnant women, and the differential diagnosis with melanoma may be challenging.